Fig. 20 in Cambrian microfossils from glacial erratics of King George Island, Antarctica ... - Wrona, Ryszard (Zenodo, 2004)
Fig. 20. Holotype of Hadimopanella staurata sp. nov., ZPAL V.VI/24S3, errratic boulder Me66. A. Oblique lateral view, stereo−pair. B. Upper view. C. Enlargement showing (in a hole) arrangement of phosphate crystallites in the external sclerite layer. ... : Published as part of Wrona, Ryszard, 2004, Cambrian microfossils from glacial erratics of King George Island, Antarctica, pp. 13-56 in Acta Palaeontologica Polonica 49 (1) on page 44, DOI: 10.5281/zenodo.13285795 ...